EFFECT OF ON MELT GRAFTING OF GL YCIDYL METHACRYLATE ONTO NATURAL RUBBER IN THE PRESENCE OF ORGANIC PEROXIDES - ., Eddiyanto (JURNAL PENELITIAN SAINTIKA, 2012)
The main aim of this work was to study of melt grafting glycidylmethacrylate (GMA) on natural rubber (NR) using reactive processing methods.Four different peroxides benzoyl peroxide (BPO), dicumyl peroxide (DCP), 2,5-dimethyl-2,5-bis-(tert-butyl peroxy) hexane (T-101), and 1,1-di(tert-butylperoxy)-3,3,5-trimethyl cyclohexane (T-29B90) were examined as free radical initiators. Anappropriate methodology was established and chemical composition and reactive processing parameters were examined and optimised. Procedures for purification ofthe reaction products were developed so that the extent of monomer grafting on the rubber can be characterised accurately, using mainly FTIR technique. The reactionmechanism of the functionalisation was also examined. It was found that thegrafting degree of GMA increased with increasing of GMAs concentration. It wasalso found that T-101 was a suitable peroxide to initiate the grafting reaction ofthese monomers on NR.